CARBONIFEROUS MARGINAL RIFTING IN GANGDESE: VOLCANIC ROCKS AND STRATIGRAPHIC CONSTRAINTS, XIZANG (TIBET), CHINA - Geng Q.; Wang L.; Pang G.; Zhu D.; Liao Z.; Li G.; Li F.; Jin Z. (My University, 2007)
As a Mesozoic and Cenozoic magmatic arc, the Gangdese zone is an important field of Tibetan geologic studies. Yet the late-Paleozoic volcanic rocks and their tectonic settings however, still remain unstudied. Based on new data of geologic survey, the authors carried out stratigraphical and geochemical studies on the Carboniferous volcano-stratigraphic sequences in the Gangdese zone. We measured key geologic sections and analysed volcanic rock samples for major and trace elements and Sr, Nd and Pb isotopes. The boundary between Carboniferous and Devonian or Precambrian rocks is an important tectonic transitional surface in the Gangdese, which represented by uncomformity or sharp contacts between different lithologies and lithofacies. There are two sedimentary cycles in the Carboniferous from littoral zone, abyssal slope to littoral zone, with two phases of volcanic eruption accompanying the abyssal slope deposits and pebbly slate of icy sea facies. Major volcanic rock types of Carboniferous times are andesitic basalt, dacite, rhyolite, characterized by a bimodal volcanic suite. Compared with typical MORB and arc basalt, the andesitic basalt has lower content of MgO and higher contents of TiO2, Al2O3, and P2O5 with REE and trace elemental normalized patterns similar to those of continental flood basalts. The silicic volcanic rocks of Carboniferous times has similar REE and trace elemental geochemistry as continental rhyolite. Geochemical and stratigraphical studies suggest that the tectonic setting of the Gangdese region is depressional rifting to the northern margin of Gondwanaland. The mantle source of volcanic rocks, with typical Dupal anomaly, experienced complex mixing process involving primitive mantle, EMII and crust rocks, which suggest subduction of older crust of Gondwanaland and then it was recycled into the mantle. Some particular chemical features of the Carboniferous basaltic rocks may relate to source rock mixing.
Keywords: CARBONIFEROUS TIMES; MARGINAL RIFTING; STRATIGRAPHY; THE GANGDESE ZONE IN TIBET; VOLCANIC ROCK GEOCHEMISTRY; Carboniferous; Devonian; Cambrian; Paleozoic::Carboniferous; Палеозой::Каменноугольная; Paleozoic::Devonian; Палеозой::Девонская; Paleozoic::Cambrian; Палеозой::Кембрийская